If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(6x + 4) = 1 + log(x + -5) Reorder the terms: glo(4 + 6x) = 1 + log(x + -5) (4 * glo + 6x * glo) = 1 + log(x + -5) (4glo + 6glox) = 1 + log(x + -5) Reorder the terms: 4glo + 6glox = 1 + glo(-5 + x) 4glo + 6glox = 1 + (-5 * glo + x * glo) 4glo + 6glox = 1 + (-5glo + glox) Solving 4glo + 6glox = 1 + -5glo + glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '5glo' to each side of the equation. 4glo + 5glo + 6glox = 1 + -5glo + 5glo + glox Combine like terms: 4glo + 5glo = 9glo 9glo + 6glox = 1 + -5glo + 5glo + glox Combine like terms: -5glo + 5glo = 0 9glo + 6glox = 1 + 0 + glox 9glo + 6glox = 1 + glox Add '-1glox' to each side of the equation. 9glo + 6glox + -1glox = 1 + glox + -1glox Combine like terms: 6glox + -1glox = 5glox 9glo + 5glox = 1 + glox + -1glox Combine like terms: glox + -1glox = 0 9glo + 5glox = 1 + 0 9glo + 5glox = 1 Reorder the terms: -1 + 9glo + 5glox = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 9glo + 5glox = 0 The solution to this equation could not be determined.
| -6r+250=-100+0.2(y-0.25y)+0.25y | | -6r+250=-100+0.2(y-0.25y) | | 8x-8=-9 | | r^2-12r-1=0 | | -[3z^2+4z-(2z^2-8z)]+[(9z^2-[5z-z^2])+5z^2]= | | -30=-6(3n-7) | | -30=6(3n-7) | | -8x+y-x+7y= | | .03x^2-9x+600=0 | | -(8-r)=-15 | | x^2+x+0.25=25 | | 3x+5x+10x=180 | | 3/4t-4=2 | | 6=-2+4(p+8) | | y/2-1=2 | | x*x-2x-5=0 | | 28=-4x+8(2x-1) | | x/3=8.1 | | 2(x+1)-4=4x-2(2+x) | | 1+5n+5=10+3n | | 6(3n-3)=(8n+6)+2 | | 50x+3n=100 | | z^2+10z=75 | | 4=4-4y-7y | | y-1=-0.75(x-1) | | (224.9/0.2)^2/3 | | -9=.16z-11 | | 3+dz=12 | | 5x+9=x+11 | | -9h-6+12+40=22 | | 5x+9=x+111 | | 15y-10=14y+13 |